Characterizing RAPIDTM platelet and leukocyte-rich plasma gels - an autologous, point-of-care medicine for diabetic foot ulcer treatment - Aleksandra Olszewska; Simon Pitchford; James Rickard; Ben Forbes (University of Huddersfield Press, 2022)
In 2017/18 wound healing cost the NHS 8.3 billion pounds. There is an urgent need for more effective, accessible, and safe treatments. Platelet-rich plasma (PRP) therapies have been emerging since the early 2000s, currently they are used across various medical fields treating conditions from cosmetic procedures through burn treatments to wound healing. RAPIDTM gel is a product for the treatment of diabetic foot ulcers that is currently in stage 2b of clinical trials. This project aims to better understand the properties of the gel and how these are affected by the manufacturing process. The PRP gels were characterized physiochemically by exploring the gel time, exudate release and growth factor content. These data provide a baseline for future studies exploring how variations in manufacturing conditions affect the gel properties.